Effectivity of the Oketani Massage and the Back Massage Combination towards Breastmilk Production and to Prevent Breast Engorgement of Postpartum Mothers - Ngestiningrum, Ayesha Hendriana; Nuryani, Nuryani; Setiyani, Astuti (Health Notions, 2022)
Breast milk is the most important baby food, especially during the first weeks of a baby's life. To help postpartum mothers with breastfeeding problems and breast engorgement, the researchers developed a combination of Oketani massage and back massage to increase breastmilk production and to prevent breast engorgement. This is quasi-experimental research designed with a pre-post test and with a control group. The research population consisted of post-partum mothers in the Lembeyan Community Health Center area, Magetan Regency, East Java with a consecutive sampling technique. The independent variable is the combination of the Oketani Massage and the Back Massage, meanwhile, the dependent variables are breastmilk production and prevention of breast engorgement in postpartum mothers. The respondents consisted of 50 people. The combination of the Oketani Massage and Back Massage is effective in increasing breastmilk production. This can be seen from the results of the independent t-test with a significance value of 0.00 (